Checklist of the genus Cybocephalus Erichson (Coleoptera: Cybocephalidae) of China, with description of a new species from Yunnan Province - Tian, Mingyi (Zootaxa, 2006)
A checklist to all known species of the genus Cybocephalus Erichson of China is presented, together with distributional data. A new species from western Yunnan Province is described and illustrated: Cybocephalus liui n. sp.